A Double-Edge Sword? Mass Media and Nonviolent Dissent in Autocracies. (March 2023) - Gleditsch, Kristian Skrede; Macías-Medellín, Martín; Rivera, Mauricio
It is often assumed that nondemocratic regimes will control mass media and suppress independent information, but in many autocracies the media are partially free and imperfectly controlled. We argue that partial media freedom can increase the prospects for mass nonviolent dissent. We develop a theory emphasizing how even less than perfectly free media outlets can increase the ability of individuals to coordinate and mobilize, and provide an informational endowment that can help non-state actors overcome collective mobilization barriers. We further argue that this informational endowment amplifies the effect of other influences spurring mass protests in autocracies, in particular protest contagion and elections. We find empirical support for our argument in an analysis of all autocracies between 1955 and 2013. A case study of the Georgian Rose revolution provides further support for the postulated mechanisms.